2017
DOI: 10.1159/000484304
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Alleviates Angiotensin II-Induced Cardiac Dysfunction and Interstitial Fibrosis in Mice

Abstract: Background/Aims: Endothelial-to-mesenchymal transition (EndMT) is a mechanism that promotes cardiac fibrosis induced by Angiotensin II (AngII). Kaempferol (KAE) is a monomer component mainly derived from the rhizome of Kaempferia galanga L. It shows anti-inflammatory, anti-oxidative, anti-microbial and anti-cancer properties, which can be used in the treatment of cancer, cardiovascular diseases, infection, etc. But, its effects on the development of cardiac remodelling remain completely unknown. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Aging increases TGF‐ß expression, which plays an important role in the synthesis and secretion of collagen by cardiac fibroblasts, thus contributing to cardiac stiffening (Nakou et al, ). Kaempferol and PC of a yacon plant were shown to alleviate, respectively, myocardial fibrosis in angiotensin II‐induced cardiac dysfunction and in diabetic rat model (Dos Santos et al, ; Liu et al, ). Nevertheless, these experiments were undergone in pathological conditions not related to normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…Aging increases TGF‐ß expression, which plays an important role in the synthesis and secretion of collagen by cardiac fibroblasts, thus contributing to cardiac stiffening (Nakou et al, ). Kaempferol and PC of a yacon plant were shown to alleviate, respectively, myocardial fibrosis in angiotensin II‐induced cardiac dysfunction and in diabetic rat model (Dos Santos et al, ; Liu et al, ). Nevertheless, these experiments were undergone in pathological conditions not related to normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibrosis is a major feature of hypertrophic cardiomyopathy and contributes to ventricular dysfunction and life-threatening arrhythmia [13,24]. Our in vivo study showed that Hyp treatment reduced the pressure overload-induced fibrotic response.…”
Section: Discussionmentioning
confidence: 51%
“…Afterwards, they adopted endothelial lineage tracing and observed the emergence of fibroblasts derived from EndMT in the process of kidney fibrosis s [27]. Interestingly, extensive research has attested that TGF-β signaling is potentially involved in the stimulation of EndMT [4, 9, 28]. Xavier et al utilized heterozygous endothelium-specific TGF-β receptor knockout mice and supported that ablating TGF-β signaling is sufficient to curtail EndMT and thereby attenuate the fibrotic responses in injured kidney [29].…”
Section: Discussionmentioning
confidence: 99%